2020
DOI: 10.3390/jrfm13070156
|View full text |Cite
|
Sign up to set email alerts
|

Time-Frequency Based Dynamics of Decoupling or Integration between Islamic and Conventional Equity Markets

Abstract: This paper investigates the decoupling and integration between the region-wise (Asia, Europe, Africa and the Americas) developed and emerging market’s equity pairs of Islamic and conventional stock returns with the focus on multi-horizons. In doing so, daily wavelet and ADCC-based stock returns correlations are estimated to capture the dynamics of time-frequency and the time-domain based correlations, respectively. The findings of this study indicate that at the short-term horizon, the all selected emerging an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Wavelets are a multi-solution-based powerful and dynamic approach that enable efforts to overcome the barriers of time-series parametric-based estimation under the Capital Asset Price Model's (CAPM) guidelines. Moreover, it explains the decoupling hypothesis and heterogeneity of asset returns by observing different risk patterns between conventional and Islamic stock markets (Anas et al 2020;Sharif et al 2020).…”
Section: Introductionmentioning
confidence: 91%
“…Wavelets are a multi-solution-based powerful and dynamic approach that enable efforts to overcome the barriers of time-series parametric-based estimation under the Capital Asset Price Model's (CAPM) guidelines. Moreover, it explains the decoupling hypothesis and heterogeneity of asset returns by observing different risk patterns between conventional and Islamic stock markets (Anas et al 2020;Sharif et al 2020).…”
Section: Introductionmentioning
confidence: 91%
“…Ahmed (2019) finds that Islamic–conventional couples are susceptible to the US economic policy uncertainty and reject the dichotomous distinction between these stock markets for all regions. Anas et al (2020) examine the decoupling and the dependence between developed and emerging Islamic and traditional market indices. Their results suggest that the decoupling hypothesis was largely rejected for all regions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, the empirical results of Chiou (2008) suggest that local investors in underdeveloped countries in East Asia and Latin America might benefit more from regional diversification than from global diversification. Even though the international market has become increasingly integrated over the past two decades (Anas et al 2020), leading to a decline in diversification benefits, investors have concluded that this finding still holds.…”
Section: Optimal Portfolio Size Across Different Capital Marketsmentioning
confidence: 99%